2008
DOI: 10.1016/s0929-6646(08)60094-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Multimodule Curriculum of Palliative Care on Medical Students

Abstract: A multimodule curriculum of palliative care for medical students can significantly improve their knowledge on principles of clinical management and beliefs about ethical decision-making in palliative care. As for changes in beliefs about ethical decision-making in palliative care, continued ethical and clinical training is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 16 publications
0
20
0
1
Order By: Relevance
“…9 12 25 Students indicated that the course taught them something new about symptom management, pain treatment, medication and opioids, as indicated elsewhere,9 11 despite the previous assertion that improvement in general knowledge was low. As in other studies, the students referred to an improvement in their communication skills, as well as in their approach to difficult situations 9 14.…”
Section: Discussionmentioning
confidence: 91%
“…9 12 25 Students indicated that the course taught them something new about symptom management, pain treatment, medication and opioids, as indicated elsewhere,9 11 despite the previous assertion that improvement in general knowledge was low. As in other studies, the students referred to an improvement in their communication skills, as well as in their approach to difficult situations 9 14.…”
Section: Discussionmentioning
confidence: 91%
“…Instead of this, end-of-life curriculum in medical school could provide the correct concepts with positive impact on medical students. 4 To enhance physicians' willingness to provide palliative care, presenting correct concepts and knowledge of palliative care through medical school education should be emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…2 Several studies have demonstrated that end-of life educational curricula and clinical training can improve medical students' knowledge and attitude toward palliative care. [3][4][5][6] Those who complete clinical rotations and courses in palliative care feel more comfortable with death and caring for dying patients. 5,7 Research on residents and fellowships show a similar result.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tsai, et al were able to implement a four-hour curriculum including a lecture, a hospice patient visit, communication skills practice, and group discussion with students in attendance from three local medical schools. 52 Because trainees' self-assessments of their skills may not predict the patient's assessment of the interaction, it is important that educators measure behavioral and patient outcomes, rather than relying solely on student assessments to demonstrate the effectiveness of a curriculum. However, in our sample the vast majority of studies (35 out of 39, 90%) measured outcomes either at the level of satisfaction, perceptions, and attitudes (usually measured by self-assessment on a Likert scale) or at the level of knowledge acquisition (usually measured by multiple-choice examination).…”
Section: Study Qualitymentioning
confidence: 99%